-->

बीजगणितीय सूत्र

बीजगणितीय सूत्र
आधारभूत सूत्र
(a+b)²=a²+b²+2ab
(a-b)²=a²+b²-2ab
a²+b²=(a+b)²-2ab
a²+b²=(a-b)²+2ab
(a+b)²-(a-b)²=4ab
(a+b)²+(a-b)²=2(a²+b²)
a²-b²=(a+b)(a-b)
(a+b)³=a³+b³+3a²b+3ab²
(a+b)³=a³+b³+3ab(a+b)
(a-b)³=a³-b³-3a²b+3ab²
(a-b)³=a³-b³-3ab(a-b)
a³+b³=(a+b)(a²-ab+b²)
a³+b³=(a+b)³-3ab(a+b)
a³-b³=(a-b)(a²+ab+b²)
a³-b³=(a-b)³+3ab(a-b)
यदि a+b+c=0,तो a³+b³+c³=3abc


घातांक एवम् करणी से सम्बंधित सूत्र
\[\begin{align} & {{a}^{m}}\times {{a}^{n}}={{a}^{m+n}} \\ & \frac{{{a}^{m}}}{{{a}^{n}}}={{a}^{m-n}} \\ & {{({{a}^{m}})}^{n}}={{a}^{mn}} \\ \end{align}\]
\[{(ab)^m} = {a^m} \times {b^m}\]

Related Posts:

Disqus Comments
© 2017 Jobs Career For You - Template Created by goomsite - Proudly powered by Blogger